Brazilian immigrants’ oral health literacy and participation in oral health care in Canada - Calvasina, Paola (BMC Oral Health, 2016)
BACKGROUND: Inadequate functional health literacy is a common problem in immigrant populations. The aim of this study was to investigate the association between oral (dental) health literacy (OHL) and participation in oral health care among Brazilian immigrants in Toronto, Ontario, Canada. METHODS: The study used a cross-sectional design and a convenience sample of 101 Brazilian immigrants selected through the snowball sampling technique. Data were analyzed using descriptive statistics and logistic regression modeling. RESULTS: Most of the sample had adequate OHL (83.1 %). Inadequate/marginal OHL was associated with not visiting a dentist in the preceding year (OR = 3.61; p = 0.04), not having a dentist as the primary source of dental information (OR = 5.55; p < 0.01), and not participating in shared dental treatment decision making (OR = 1.06; p = 0.05; OHL as a continuous variable) in multivariate logistic regressions controlling for covariates. A low average annual family income was associated with two indicators of poor participation in oral health care (i.e., not having visited a dentist in the previous year, and not having a dentist as regular source of dental information). CONCLUSION: Limited OHL was linked to lower participation in the oral health care system and with barriers to using dental services among a sample of Brazilian immigrants. More effective knowledge transfer will be required to help specific groups of immigrants to better navigate the Canadian dental care system.